Non-adherence to antidiabetic medications and associated factors among adult type 2 diabetes mellitus patients in Northeast Ethiopia: institutional based cross-sectional study - Abebe Tarekegn Kassaw; Fentaw Girmaw; Getachew Ashagrie; Tenaw Baye Tarekegn; Abebech Derbie; Ayelgn Mengesha (BMJ Open)
Background Non-adherence to antidiabetic medication remains a major barrier to achieve optimal health outcomes among individuals with diabetes, particularly in developing countries. This issue exacerbates poor health outcomes and leads to the wastage of limited healthcare resources.Objective This study aimed to assess the prevalence of non-adherence to antidiabetic medications and identify associated factors among adult type 2 diabetes mellitus (DM) patients in the North Wollo zone.Study design An institutional-based cross-sectional study.Setting The study was conducted in three randomly selected public hospitals in the North Wollo zone: Woldia Comprehensive Specialized Hospital, Lalibela General Hospital and Mersa Primary Hospital.Participants A total of 327 adult type 2 DM patients receiving follow-up care were included. Participants were selected proportionally from each hospital using consecutive sampling. Inclusion criteria included individuals aged ≥18 years, on antidiabetic treatment for at least 6 months and actively on follow-up care during the study period. Patients with hearing impairment, severe illness or incomplete medical records were excluded.Main outcome measures Adherence was assessed using the Morisky Medication Adherence Scale-8, a validated eight-item, self-reported questionnaire. Scores ranged from 0 to 8, with adherence levels classified as high (≥8), medium (6–7.75) and low (<6). Patients scoring ≥6 were considered adherent, while those scoring <6 were non-adherent.Statistical analysis Data were analysed using SPSS V.27. Descriptive statistics were used to summarise the data, and multivariable logistic regression analysis was performed to identify factors associated with non-adherence. A p value ≤0.05 was considered statistically significant.Results The overall prevalence of medication non-adherence was 24.5%. Factors significantly associated with non-adherence included living with diabetes for less than 3 years (adjusted OR (AOR) 3.37, 95% CI 1.91 to 5.95), residing in rural areas (AOR 2.67, 95% CI 1.49 to 4.79), having comorbidities (AOR 2.99, 95% CI 1.67 to 5.34) and having no formal education (AOR 3.26, 95% CI 1.49 to 7.00).Conclusion The prevalence of non-adherence to antidiabetic medications (24.5%) exceeded the widely accepted benchmark of ≤20%. Key factors such as rural residence, comorbidities, lower education levels and shorter duration since diagnosis were significantly associated with non-adherence. These findings underscore the need for targeted interventions, including patient education, improved rural healthcare access and integrated care models, to enhance adherence and diabetes management outcomes.